Tetanus Immunization - Uzma Ghori; Fasia Basir; Gul Ahuja; Amir Ashraf (ziauddin University, 2024)
Background: A high prevalence rate of neonatal and adult tetanus in Pakistan reflects the failure of health care systems to provide adequate immunization. Health care workers (HCWs) of emergency departments (ED) are generally at the frontline to deal with patients of road traffic accidents, trauma and burns. However, it has been observed that these patients receive incomplete preventive measures to combat tetanus. Objective: To assess the knowledge of tetanus immunization among healthcare workers (HCW) of the emergency department (ED) at a tertiary care hospital. Methods: A cross sectional study was conducted on 104 HCWs of ED of Ziauddin University. A structured questionnaire was filled by HCWs during April and May 2014. Data were analyzed on SPSS 20.0. Categorical variables were presented as frequency and percentage, while continuous variables were presented as mean. P value of <0.05 was considered significant. Results: Total 104 HCWs from ED participated in the study. Only 11.8% (12) HCWs were aware of the correct dosing schedule in children under 12 years of age. 56.3% (58) and 68% (70) were aware of correct schedule in adult population and in pregnant females, respectively. Knowledge of tetanus immunization in different types of wounds according to previous immunization status of patients was also found inadequate. Conclusion: HCWs of ED have inadequate knowledge about tetanus prone injuries and its immunization, which needs to be addressed. Key Words: Tetanus, Immunization, Emergency Department, Healthcare Workers.